2005
DOI: 10.1037/0090-5550.50.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Positive Coping and Stress-Related Psychological Growth Following Lower Limb Amputation.

Abstract: To present a cross-sectional qualitative exploration of how individuals cope with a lower limb amputation and to examine the influence of positive coping and stress-related psychological growth on adjustment. Participants: 12 patients with a lower limb amputation. Setting: Artificial Limb and Appliance Centre in South Wales, United Kingdom. Design: Semistructured interviews, using grounded theory for analysis. Measures: The Hospital Anxiety and Depression Scale (A. Zigmond & R. Snaith, 1983) and the Rosenberg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
60
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 68 publications
5
60
0
3
Order By: Relevance
“…This determined attitude has been described in other studies; for example, Oaksford et al [23] noted that patients needed to feel a sense of control over their situation and often dealt with the traumatic event of an amputation by trying to look towards the future in a positive way. The implications of not maintaining this attitude may be added to the adjustment concerns faced by the new amputee.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…This determined attitude has been described in other studies; for example, Oaksford et al [23] noted that patients needed to feel a sense of control over their situation and often dealt with the traumatic event of an amputation by trying to look towards the future in a positive way. The implications of not maintaining this attitude may be added to the adjustment concerns faced by the new amputee.…”
Section: Discussionmentioning
confidence: 54%
“…This is supported by a number of studies. Oaksford et al [23] suggested that established amputees are seen as credible informants and that access to them should be a standard part of rehabilitation. Gallagher and MacLachlan [22] suggest amputees may act as positive role models helping patients who are new amputees, to believe they could achieve the same things.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be because most studies used questionnaires and very few are based on an inductive process to uncover coping strategies specific to lower limb amputations. In a grounded theory proposed by Oaksford et al [30], humor was identified as a coping strategy to deal with disability within the first 6 months, one year, and five years following transtibial amputation. On the other hand, Rybarczyk, Nicholas, and Nyenhuis [31] conceptualized humor as a tool that facilitates coping but not as a coping strategy.…”
Section: Discussionmentioning
confidence: 99%